2013
DOI: 10.1016/j.aquatox.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of agricultural inputs into a Mediterranean coastal lagoon (Mar Menor, SE Spain) on transplanted clams (Ruditapes decussatus) by biochemical and physiological responses

Abstract: The Mar Menor is a coastal lagoon threatened by the development of intensive agriculture in the surrounding areas. Large amounts of pesticides from these areas are discharged into El Albujón, a permanent watercourse flowing into the lagoon. We have used a multi-biomarker approach to assess the biological effects of agricultural pollution on a bivalve species. Biomarkers indicative of neurotoxicity (acetylcholinesterase, AChE), oxidative stress (catalase, CAT; glutathione reductase, GR and lipid peroxidation, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 76 publications
2
29
1
Order By: Relevance
“…The IBR approach has also been widely used to investigate both native and caged bivalves in many studies (Leinio and Lehtonen, 2005;Campillo et al, 2013;Marigomez et al, 2013aMarigomez et al, , 2013b. In this study, IBR/n showed a significant difference among the sampling sites, with XZ site having the highest IBR/n value of 3.58.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The IBR approach has also been widely used to investigate both native and caged bivalves in many studies (Leinio and Lehtonen, 2005;Campillo et al, 2013;Marigomez et al, 2013aMarigomez et al, , 2013b. In this study, IBR/n showed a significant difference among the sampling sites, with XZ site having the highest IBR/n value of 3.58.…”
Section: Discussionmentioning
confidence: 65%
“…However, the CAT activity of oysters from XZ was significantly inhibited compared to other sites, which was likely related to higher levels of heavy metals at this site. Previous studies have recorded that mussels caged in the polluted sites showed lower CAT activity than that in the reference mussels (Viarengo et al, 2007;Campillo et al, 2013). On the other hand, the oxidative stress in organisms may also induce lipid peroxidation, resulting in increased MDA level (Kamel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them have been used to reveal the exposure to a wide range of pollutants, both metals and organic compounds (Campillo et al, 2013;Fernández et al, 2010Fernández et al, , 2012Regoli, 1998;Akosan et al, 1997). SOD is the enzyme responsible of the formation of hydrogen peroxide H 2 O 2 , after removal of the superoxide anion (O 2 − ) (Regoli and Giuliani, 2014), which makes necessary its coordination with other H 2 O 2 enzymes such as CAT, which is an extremely active catalyst for reduction of H 2 O 2 to H 2 O at high levels of H 2 O 2.…”
Section: Introductionmentioning
confidence: 97%